Analisis Perbandingan Rencana Anggaran Biaya ( RAB ) dengan Rencana Anggaran Pelaksanaan ( RAP ) Pada Pembangunan Gedung Serba Guna SIT Insan Mulia Manokwari: Comparative Analysis Of The Cost Budget Plan (Rab) With TheImplementation Budget Plan (Rap) For The Construction Of TheSit Insan Mulia Manokwari Multipurpose Building - Alief Nusantara Nur; Indra Birawaputra; Sudarman (JISTECH: Journal of Information Science and Technology, 2026)
This study discusses the comparative analysis of the cost budget in the SIT Insan Mulia Manokwari Multipurpose Building Construction Project, using two budget plan documents in the success of the construction project to balance the parameters of cost, time, and quality. The difference in estimated values between the planner's contract RAB and the contractor's RAP often causes large deviations due to differences in volume reference standards, labor wages, and market price fluctuations. This study aims to calculate the total RAP value, analyze the amount of financing deviation, and identify the dominant components causing the difference in the SIT Insan Mulia Manokwari Multipurpose Building Construction Project. This study uses a quantitative method with a descriptive-comparative approach. Secondary project data were collected in the form of shop drawings and Bill of Quantities (BoQ) documents of the planning contract. Meanwhile, primary data were obtained through material price surveys at local distributors and actual labor wages in the field. Comparisons were carried out using pairwise comparisons to review in depth the cost disparities in each component of the work item. The comparative analysis results show that the RAB value is IDR.2,690,333,000.00 while the RAP is IDR.1,641,274,000.00, so there is a deviation of IDR.1,049,059,000.00 or 38.99%. This cost difference is triggered by the direct material procurement strategy, the implementation of worker productivity wages, minimizing material waste, and optimizing the reuse of wooden formwork up to 3-4 times.